Hyaluronic acid for biomedical and pharmaceutical applications - Collins, Maurice N. (Smithers Rapra, 2014)
Hyaluronic acid (HA) is found in extracellular tissue in many parts of the body. It is a material of increasing importance to biomaterials science and is finding applications in diverse areas ranging from tissue culture scaffolds to cosmetic materials. Its properties, both physical and biochemical, in solution or hydrogel form, are extremely attractive for various technologies concerned with body repair. This book considers the materials science behind some of the important biomedical and therapeutic applications that are emerging for HA. Key characteristics such as its mechanical properties,